Relações interpessoais na sala de aula: encontros e desencontros com base no pensamento educacional de Alfonso López Quintás e análise do filme mentes perigosas - Costa, Maria Aparecida Mazaro da (2008)
The conflict’s relations present in the school universe nowadays have became more and more constant. What we can see, today, in the classroom is a disagreement of ideas and ideals that brings, so many times, to this space a desolated scenery where students and educators seem to be “competitors” measuring their strength and power, without paying attention to the educational damages that this situation produces. Innumerable are the studious and specialist of education who have leaned over backwards to this subject trying to diminish the damages on the integral formation of children and young people originated from this educational context. In this enviroment, this paper searched out on the Spanish educator and philosopher Alfonso López Quintás’s work, the concept of Encounter, suggesting an analysis on issues related to the interpersonal relationships in the school universe, more specifically in the classroom. Agreement and Disagreements. Enchantments and disenchantments. Friendships and conflicts. Though the view of Alfonso López Quintás’s thoughts, this focus on the interpersonal relationships in the classroom - possible agreements, undesirable disagreements, is verified in the analysis of the movie Dangerous Minds.